Examining Government Preference for Enhancing Islamic Education Through Regulatory Review - Rizal, Muhammad; Zahriyanti, Zahriyanti; Bahar, Herwina (AL-ISHLAH: Jurnal Pendidikan, 2024)
Government regulations on Islamic education in Indonesia have provided significant clarity and fulfilled educational needs within a developing society. These regulations demonstrate democratic, cultural, and adaptable qualities in the legal framework of Islamic education. However, challenges remain in achieving parity between Islamic and general education policies. This research employed a literature review approach, analyzing data from books, scientific articles, and research reports. A comparative and historical analysis was conducted to assess the impact of government policies on Islamic education. The findings reveal three key outcomes: (1) Government policies have shaped Islamic education to help students understand and practice their religious teachings across various levels of general education; (2) The Ministry of Religion has been granted autonomy to determine Islamic education curriculum policies; and (3) Political efforts to equalize the status of Islamic education with general education have encountered significant challenges, hindering policy development. The research highlights the ongoing struggle to integrate Islamic education within the broader educational system, which continues to present obstacles for policymakers. Despite these challenges, the autonomy granted to the Ministry of Religion marks progress in shaping the curriculum according to Islamic values. The study provides valuable insights for policymakers and stakeholders, offering guidance on improving Islamic education policies in Indonesia. Further efforts are necessary to address the political challenges that affect the development and implementation of Islamic education laws.